Carbon-coated Na3V2(PO4)2F3 nanoparticles embedded in a mesoporous carbon matrix as a potential cathode material for sodium-ion batteries with superior rate capability and long-term cycle life. Issue 43 (1st October 2015) - Liu, Qiang; Wang, Dongxue; Yang, Xu; Chen, Nan; Wang, Chunzhong; Bie, Xiaofei; Wei, Yingjin; Chen, Gang; Du, Fei
Abstract : The HRTEM image and long-term cycle life with capacity retentions of 70% and 50% over 1000 and 3000 cycles at 10C and 30C rates, respectively. Abstract : A carbon-coated Na3 V2 (PO4 )2 F3 nanocomposite (NVPF@C) is successfully realized by a facile sol–gel method. Carbon-coated NVPF nanoparticles are dispersed inside the mesoporous carbon matrix, which can not only improve the electron/ion transfer among different nanoparticles, but also benefit the electrolyte wetting during cycling. As a result, the NVPF@C cathode demonstrates remarkable Na + storage performance: a high reversible capacity of nearly 130 mA h g −1 over 50 cycles between 4.3 and 2.0 V; superior rate capability with specific capacities of nearly 74 and 57 mA h g −1 at high current densities of 15C (1.92 A g −1 ) and 30C (3.84 A g −1 ), respectively; long-term cycle life with capacity retentions of 70% and 50% over 1000 and 3000 cycles at 10C and 30C rates. Thanks to the manifested high energy and power densities, the NVPF@C nanocomposite is suggested as a promising cathode material for grid energy storage.